2007
DOI: 10.4269/ajtmh.2007.76.1189
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Chikungunya Virus Infection on Grande Comore Island, Union of the Comoros, 2005

Abstract: An outbreak of Chikungunya virus (CHIKV) illness associated with high fever combined with prolonged and severe arthralgias occurred on Grande Comore Island from January through May 2005; 5,202 cases were reported. A seroprevalence study was conducted to define the extent of transmission on the island. We conducted a cross-sectional survey using a multistage sampling technique. A total of 481 households were sampled. In each household, one resident was selected randomly for interview and blood collection. We ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
119
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(135 citation statements)
references
References 11 publications
8
119
3
5
Order By: Relevance
“…Par la suite, de nouvelles Ă©pidĂ©mies ont Ă©tĂ© dĂ©cri-tes dans ce pays ainsi qu'aux Cambodge, Vietnam, Laos, Myanmar, Philippines, Inde et IndonĂ©sie (Jupp & McIntosh, 1988;Johnston & Peters, 1996). AprĂšs 20 ans d'absence, le virus est rĂ©apparu Ă  Java, en IndonĂ©sie, en 2001(Laras et al, 2005 (Sergon et al, 2007). La circulation du CHIKV parmi les Ăźles de la zone SOOI ne semble cependant pas nouvelle puisque la prĂ©sence du virus avait dĂ©jĂ  Ă©tĂ© notifiĂ©e aux Seychelles en 1979 (Calisher et al, 1981).…”
Section: Mise Au Pointunclassified
“…Par la suite, de nouvelles Ă©pidĂ©mies ont Ă©tĂ© dĂ©cri-tes dans ce pays ainsi qu'aux Cambodge, Vietnam, Laos, Myanmar, Philippines, Inde et IndonĂ©sie (Jupp & McIntosh, 1988;Johnston & Peters, 1996). AprĂšs 20 ans d'absence, le virus est rĂ©apparu Ă  Java, en IndonĂ©sie, en 2001(Laras et al, 2005 (Sergon et al, 2007). La circulation du CHIKV parmi les Ăźles de la zone SOOI ne semble cependant pas nouvelle puisque la prĂ©sence du virus avait dĂ©jĂ  Ă©tĂ© notifiĂ©e aux Seychelles en 1979 (Calisher et al, 1981).…”
Section: Mise Au Pointunclassified
“…In 2005, CHIKV emerged in Comoros (Sergon et al, 2007) followed by Reunion Island, the Seychelles, Mauritius and Mayotte. In Reunion Island alone, more than a third of the total population (267 000 individuals) was debilitated (Schuffenecker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1,11 The high seroprevalence of anti-CHIKV IgM antibodies (62.2%) and attack rate (58.3%) observed in the present study is comparable with the figures documented during earlier outbreaks in Africa, Grande Comore Island, and other parts of India. [12][13][14] However, the seroprevalence studies done in these territories have shown large variations between regions in the prevalence rate. 15 It was 38.2% in La Reunion Island and 63% in Grande Comore Island.…”
mentioning
confidence: 99%
“…15 It was 38.2% in La Reunion Island and 63% in Grande Comore Island. 13,15 The current serosurvey was conducted at the end of outbreak, avoiding the risk of underestimating the number of cases that might occur if serosurveys are conducted during epidemic.…”
mentioning
confidence: 99%